Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Pelanggan pada Pelanggan Premium PT. PLN (Persero) UP3 (Unit Pelaksana Pelayanan Pelanggan) Padang - Dunnas, Irsyad; Afrizoni, Hosra (Fakultas Ekonomi, Universitas Ekasaktii, 2023)
This study aims to analyze and determine the Effect of Service Quality Dimensions on Customer Satisfaction of Premium Customers of PT. PLN (Persero) UP3 (Customer Service Implementation Unit) Padang. The type of data is qualitative data which is used as quantitative data with primary data sources. Methods of data analysis in this study using descriptive analysis, multiple linear regression analysis, coefficient of determination, hypothesis testing t-test, and F test. The results of this study indicate that: 1. Reliability partially has a positive and significant effect on customer satisfaction on Premium Customers of PT. PLN (Persero) UP3 (Customer Service Implementation Unit) Padang. 2. Responsiveness partially has a positive and significant effect on customer satisfaction on Premium Customers of PT. PLN (Persero) UP3 (Customer Service Implementation Unit) Padang. 3. Assurance partially has a positive and significant effect on customer satisfaction on Premium Customers of PT. PLN (Persero) UP3 (Customer Service Implementation Unit) Padang. 4. Empathy partially has a positive and significant effect on customer satisfaction on Premium Customers of PT. PLN (Persero) UP3 (Customer Service Implementation Unit) Padang. 5. Physical evidence partially has a positive and significant effect on customer satisfaction at Premium Customers of PT. PLN (Persero) UP3 (Customer Service Implementation Unit) Padang. 6. Reliability (X1), responsiveness (X2), assurance (X3), empathy (X4) and tangibles (X5) simultaneously have a positive and significant effect on customer satisfaction on Premium Customers of PT. PLN (Persero) UP3 (Customer Service Implementation Unit) Padang.